Causal effects of 731 immune cell phenotypes on autism spectrum disorder: a Mendelian randomization study - Yu, Yunfeng; Yang, Xinyu; Hu, Gang; Yin, Yuman; Yu, Rong (Frontiers in Psychiatry, 2024)
Objective: The role of different immune cells in autism spectrum disorders (ASD) is still controversial. The purpose of this study was to evaluate the causal effects of different immune cells on ASD via Mendelian randomization (MR). Methods: Datasets of immune cell phenotypes were obtained from the European Bioinformatics Institute, and datasets of ASD were obtained from the IEU Open GWAS project. Single nucleotide polymorphisms were selected based on the assumptions of association, independence, and exclusivity. Inverse variance weighted was utilized as the main method for MR analysis. MR-Egger was employed to assess the horizontal pleiotropy of the results. Cochran's Q and leave-one-out method were used for heterogeneity analysis and sensitivity analysis of the results, respectively. Results: MR analysis showed that TD CD8br AC (odds ratio [OR] 1.137, 95% confidence interval [CI] 1.031-1.254, p = 0.010), CD8br %leukocyte (OR 1.142, 95% CI 1.067-1.223, p < 0.001), CD8br and CD8dim %leukocyte (OR 1.117, 95% CI 1.032-1.210, p = 0.006), Naive CD8br %T cell (OR 1.052, 95% CI 1.004-1.104, p = 0.035), CD28- CD8dim %T cell (OR 1.097, 95% CI 1.038-1.158, p < 0.001), CD127- CD8br AC (OR 1.086, 95% CI 1.006-1.171, p = 0.034), CD45 on CD8br (OR 1.059, 95% CI 1.021-1.099, p = 0.002), CD3 on HLA DR+ CD8br (OR 1.098, 95% CI 1.041-1.158, p < 0.001), CD4 on activated Treg (OR 1.048, 95% CI 1.001-1.096, p = 0.046), CD3 on CD39+ resting Treg (OR 1.070, 95% CI 1.012-1.131, p = 0.018), IgD+ CD38- %lymphocyte (OR 1.103, 95% CI 1.023-1.190, p = 0.011), CD62L- plasmacytoid DC %DC (OR 1.046, 95% CI 1.001-1.093, p = 0.046), and FSC-A on plasmacytoid DC (OR 1.075, 95% CI 1.003-1.153, p = 0.042) were associated with increased genetic susceptibility to ASD. MR-Egger displayed no horizontal pleiotropy (p ≥ 0.05). Cochran's Q revealed no heterogeneity of results (p ≥ 0.05). Sensitivity analysis indicated that the results were robust. Conclusion: This MR analysis revealed 13 immune cells associated with increased genetic susceptibility to ASD and emphasized the importance of CD8 T cells and Tregs, which provides new directions for the pathogenesis and drug research of ASD.